PkM Edukasi Pencegahan Kekerasan Seksual pada Remaja di SMA Swasta Kabupaten Bandung - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim (Universitas Nurul Jadid, 2023)
Sexual violence often occurs in children and adolescents and the number continues to increase from year to year. Sexual violence can have various negative impacts on victims, both physiologically, emotionally and psychologically. To prevent sexual violence in adolescents, they must be provided with the right knowledge and information regarding sex education, including the prevention of sexual violence. The purpose of this community service is to increase youth knowledge about preventing sexual violence through education. The method used was in the form of health education with an offline-based approach, the participants consisted of 54 students of class X and XI of private high schools in Bandung Regency. This activity is carried out through several stages, namely: the preparation stage; planning; implementation and follow-up plans. To determine the effectiveness of education conducted pre-test and post-test. After the education was carried out there was an increase in knowledge, namely the average pre-test knowledge was 75.19. and post-test 92.31, there is an effect of education on adolescents' knowledge about sexual prevention p-value = 0.001. Sexual prevention education for adolescents can increase adolescent knowledge. It is hoped that the school will cooperate with health workers to provide continuous health education so that students avoid sexual violence.